Does Writing Have a Future? - Flusser, Vilem, 1920-1991 (Book collections on Project MUSE., 2011)
This title asks what will happen to thought and communication as written communication gives way, inevitably, to digital expression. In the introduction, it proposes that writing does not, in fact, have a future because everything that is now conveyed in writing - and much that cannot be - can be recorded and transmitted by other means. The balance of this book teases out the nuances of these developments.